2019
DOI: 10.1186/s13578-019-0277-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Growth inhibition and apoptosis in colorectal cancer cells induced by Vitamin D-Nanoemulsion (NVD): involvement of Wnt/β-catenin and other signal transduction pathways

Abstract: BackgroundMore than the two decades, the question of whether vitamin D has a role in cancer frequency, development, and death has been premeditated in detail. Colorectal, breast, and prostate cancers have been a scrupulous spot of center, altogether, these three malignancies report for approximately 35% of cancer cases and 20% of cancer demises in the United States, and as such are a chief public health apprehension. The aim was to evaluate antitumor activity of Vitamin D-Nanoemulsion (NVD) in colorectal cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…A number of findings indicate that 1,25‐dihydroxyvitamin D 3 can stimulate differentiation and suppress proliferation in several cell types . In addition to the suppression of proliferation, 1,25‐dihydroxyvitamin D 3 can also affect viability . The effects may vary in different cells and under different conditions.…”
Section: Vitamin D and Inhibition Of Cellular Proliferation: A Role Imentioning
confidence: 99%
See 2 more Smart Citations
“…A number of findings indicate that 1,25‐dihydroxyvitamin D 3 can stimulate differentiation and suppress proliferation in several cell types . In addition to the suppression of proliferation, 1,25‐dihydroxyvitamin D 3 can also affect viability . The effects may vary in different cells and under different conditions.…”
Section: Vitamin D and Inhibition Of Cellular Proliferation: A Role Imentioning
confidence: 99%
“…The effects may vary in different cells and under different conditions. Studies examining vitamin D‐dependent responses have, in some cases, indicated a protective role and, in others, a stimulation of apoptosis . However, the reported suppression on proliferation and survival in many cell types has led to an interest in vitamin D administration as a possible treatment to counteract tumour growth or reduce cancer risk …”
Section: Vitamin D and Inhibition Of Cellular Proliferation: A Role Imentioning
confidence: 99%
See 1 more Smart Citation
“…Anticancer activity of vitamin D has been largely studied in different types of tumors, elucidating its pivotal role in cancer progression and invasion [ 134 ]. It has been reported that vitamin D inhibits colorectal, prostate and breast cancer cells growth by controlling cell proliferation [ 11 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ] through cell cycle arrest [ 144 , 147 , 148 , 149 , 150 ], by regulating cell death through apoptosis [ 54 , 144 , 147 , 151 , 152 , 153 ] and autophagic processes [ 154 , 155 ], and by modulating inflammatory processes implicated in immune infiltration and tumor invasiveness [ 134 , 137 , 150 ].…”
Section: Vitamin D and Cancer: Molecular Mechanisms In In Vivo Andmentioning
confidence: 99%
“…Vitamin D is a prohormone acts on the nuclear receptor and has pleiotropic effects beyond its nutriceutical actions. Experimental studies carried on the cancer cell lines showed that vitamin D is cytotoxic against cancer cells by inducing apoptosis [17,18]. In human, the vitamin D reduces the risk of cancers and maintains high serum levels of vitamin D in cancer-patients which improve the survival rate [19].…”
Section: Introductionmentioning
confidence: 99%